Digital resonant control of power converters under variable grid frequency conditions - Ijaz, Muhammad; Nazir, Rabia; Alhussein, Musaed; Ahmad, Jameel; Aurangzeb, Khursheed; Saleem, Faisal (Frontiers in Energy Research, 2023)
Introduction: The proportional resonant (PR) controller is known for its ability to effectively regulate sinusoidal current and voltage with low steady-state error. However, in the context of digital power systems, where operations are discrete in time, applying conventional PR controllers directly presents challenges. This study investigates the impact of various discretization methods on the performance of PR controllers, particularly under scenarios with varying reference frequencies. Methods: To assess the performance of digital PR controllers under varying reference frequency conditions, three discretization techniques are employed: zero-order hold (ZOH), impulse invariant (II), and zero pole matching (ZPM), in addition to the conventional deadbeat controller. These controllers are tested in conjunction with a single-phase pulse-width modulated (PWM) inverter, which is a crucial component in modern power systems. Results: Simulation results indicate the effectiveness of the different digital PR controllers in tracking both fixed and variable reference frequency signals while minimizing total harmonic distortion (THD) and steady-state error. When utilizing only the deadbeat controller, steady-state error and THD are measured at 4.9 V and 4.82%, respectively. However, the proposed ZPM-based digital PR controller significantly improves performance, reducing steady-state error to 0.12 V and THD to 0.45%, highlighting its superior performance. Discussion: The findings of this study emphasize the importance of choosing the appropriate discretization method when implementing PR controllers in digital power systems. The ZPM-based digital PR controller proves to be highly efficient in regulating power converters under varying grid frequency conditions. This research contributes to the understanding of digital PR controller behavior and its potential for improving power system performance, especially in scenarios with intermittent renewable energy resources and fluctuating grid frequencies.